Global Infectious Diseases in December 2022: Monthly Analysis - Qi Xiang; Taihan Li; Minjing He; Shuqiong Zhang; Yi Luo; Jiazhen Zou; Guodan Li; Qun Su; Shiping He; Wenjin Yu; Dayong Gu (Zoonoses)
The emergence and reoccurrence of infectious diseases constitute a significant threat to human health. Data for this paper were mainly obtained from official websites, such as the WHO and national CDC websites. The report summarizes and analyzes information on infectious diseases for early outbreak monitoring from 24 November to 23 December 2022. Monkeypox cases declined in December 2022 with few deaths, while cholera infections have increased in African regions and war-torn countries. Most sub-Saharan countries are affected by insect-borne diseases, such as dengue, Lassa, and chikungunya fever.